Management and Exploitation Of Mineral and Coal Mining In Indonesia: An Analysis Of the Perspective Of Article 33 Paragraph (3) of The 1945 Constitution Republic Of Indonesia - Widiarti, Wulan; Hasibu, Fauzie Yusuf; Darodjat, Tubagus Achmad (Journal Evidence Of Law, 2025)
Abstract This study analyses the implementation of mineral and coal mining management policies in Indonesia in the context of Article 33 paragraph (3) of the 1945 Constitution, which emphasises that natural resources must be used to the greatest extent for the prosperity of the people. The change from the Contract of Work regime to the Mining Business Permit (IUP) aims to strengthen state control, but still faces challenges in the form of overlapping licences, weak supervision, and social conflicts with indigenous peoples. Using the approaches of welfare state theory, middle ground theory, and development law theory, this study shows that an active role for the government is needed to ensure equitable benefit distribution and sustainable resource management. The middle ground approach highlights the need for strict oversight of foreign investment, while development law emphasises the importance of law as an instrument to support social welfare and environmental protection. This research recommends strengthening oversight, renegotiating contracts and involving local communities in mining policy to realise more equitable, sustainable and inclusive natural resource management.